Impact Performance Evaluation of a Crash Cushion Design Using Finite Element Simulation and Full-Scale Crash Testing - Büyük, Murat; Atahan, Ali Osman; Kurucuoğlu, Kenan (MDPI AG, 2018)
Crash cushions are designed to gradually absorb the kinetic energy of an impacting vehicle and bring it to a controlled stop within an acceptable distance while maintaining a limited amount of deceleration on the occupants. These cushions are used to protect errant vehicles from hitting rigid objects, such as poles and barriers located at exit locations on roads. Impact performance evaluation of crash cushions are attained according to an EN 1317-3 standard based on various speed limits and impact angles. Crash cushions can be designed to absorb the energy of an impacting vehicle by using different material deformation mechanisms, such as metal plasticity supported by airbag folding or damping. In this study, a new crash cushion system, called the ulukur crash cushion (UCC), is developed by using linear, low-density polyethylene (LLDPE) containers supported by embedded plastic energy-absorbing tubes as dampers. Steel cables are used to provide anchorage to the design. The crashworthiness of the system was evaluated both numerically and experimentally. The finite element model of the design was developed and solved using LS-DYNA (971, LSTC, Livermore, CA, USA), in which the impact performance was evaluated considering the EN 1317 standard. Following the simulations, full-scale crash tests were performed to determine the performance of the design in containing and redirecting the impacting vehicle. Both the simulations and crash tests showed acceptable agreement. Further crash tests are planned to fully evaluate the crashworthiness of the new crash cushion system.
Keywords: Medicine (General); En 1317; T55-55.3; linear, low-density polyethylene; crash cushion; simulation; TA401-492 Materials of engineering and construction. Mechanics of materials; LS-DYNA; TA630-695 Structural engineering (General); R5-920; Industrial safety. Industrial accident prevention; energy absorption; road safety; crash test